Micromechanical Properties of Gd3Ga5O12 Crystals Irradiated with Swift Heavy Ions - Aralbayeva, G.M.; Manika, Ilze; Karipbayev, Zh.; Suchikova, Y.; Kovachov, S.; Sugak, D.; Popov, Anatoli I. (Sumy State University, 2023)
This study investigated the optical absorption and mechanical behavior of Gd3Ga5O12 (GGG) single crystals exposed to fast 84 Kr ions at fluences ranging from 1013 to 1014 ion/cm2. We observed that the optical absorption spectra of GGGs grown using the Czochralski method feature distinct narrow lines in the UV spectrum, attributable to the 4f-4f transitions in Gd3+. Clear changes were identified from the 6S 7/2 base state to the 6P, 6J, and 6D states within the Gd3+ cation. An unexpected absorption band was also detected at 350 nm, likely resulting from unintentional Ca contamination. After ion exposure, the fundamental absorption edge shifted by approximately 30 nm towards the longer-wavelength section of the spectrum. Our hardness tests indicated a softening effect post-ion exposure, possibly linked to ion-triggered amorphization.
This research has been funded by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan (Grant No. AP14870696). In addition, the research of A.P. and Y.S. was partly supported by COST Action CA20129 “Multiscale Irradiation and Chemistry Driven Processes and Related Technologies” (MultIChem). A.P. thanks to the Institute of Solid-State Physics, University of Latvia. ISSP UL as the Center of Excellence is supported through the Framework Program for European universities, Union Horizon 2020, H2020-WIDESPREAD-01–2016–2017-TeamingPhase2, under Grant Agreement No. 739508, CAMART2 project.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Gd3Ga5O12 (GGG) single crystal; Swift heavy ion (6); Radiation damage; Amorphization